PERILAKU GENERASI Z TERHADAP PENGGUNAAN MEDIA SOSIAL TIKTOK: TikTok Sebagai Media Edukasi dan Aktivisme - Fadhlizha Izzati Rinanda Firamadhina; Hetty Krisnani (Universitas Padjadjaran, 2020)
Social media is widely a common thing for everyday lives now, Even some people cannot live without it. One of the most downloaded applications in 2020 now is TikTok and they change the game in social media with its 15-60 duration videos. No wonder the impact it has on multiple sectors in the world. But can TikTok operate in the education sector? In this article, the writer will analyze Generation Z's behavior towards TikTok used as educational media and activism. The intervention methods used in this article are with literature review. Results found that TikTok can be used as a form of informal education and digital activism. Informal education, it is found that a model of learning and policy is needed to have its effect on activities. To conclude, social media usage in educational sectors is indeed beneficial, but it needs more further research and models for its applications in its activities.